Analisis kewenangan pengadilan tata usaha negara (studi putusan ptun jakarta nomor. 604/g/2023/ptun jkt) - Ariani, Fira (Maliki Interdisciplinary Journal, 2025)
The State Administrative Court (PTUN) has an important role in overseeing and assessing the validity of decisions issued by state administrative bodies or officials. The authority possessed by the PTUN is crucial especially in cases involving public rights, where state administrative decisions have the potential to affect the lives of many people. This research aims to analyze the authority possessed by the State Administrative Court, especially in deciding case No. 604/g/2023/ptun. 604/G/2023/PTUN JKT. The results of this study show that the State Administrative Court has the authority to cancel or justify a state administrative decision that is proven to violate the law or unfairly harm certain parties. In case number 604/G/2023/PTUN JKT, the panel of judges decided that the decision challenged by the plaintiff met the requirements to be annulled because there was evidence that the decision was taken without regard to legal procedures or had unfairly violated the plaintiff’s rights.